Development of 21st century skills tests instrument on momentum and impulse materials - I Ma’rifatillah; R Effendi; L Hasanah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Critical and creative thinking skill are part fundamental skills in the 21st century inaddit ion collaboration and communication skill. Students’ crit ical and creat ive thinking skill isdefined as students’ abilit ies to use their knowledge to solve the daily life problems. This studymain goal is to develop a test instrument of senior high school students’ crit ical and creativethinking skills on momentum and impulse concepts. The test items are arranged based on criticaland creative thinking skills indicator that proposed by P21st Century Skill. Indicator that used inthis test are elaborate, refine, analyze and evaluate their own ideas; effectively analyze andevaluate evidence, arguments, claims and beliefs; analyze and evaluate major alternative pointsof view. This study used 4D model of research and development method. Eight test sets aredesigned based on three critical and creative thinking skill indicators that grouped to momentumand impulse concept. The result of instrument development shows all test items are valid throughPearson moment correlation coefficient test. Based on expert judgment and data collections, thetest instruments were well developed and could be used to measure students’ critical and creat ivethinking skills on momentum and impuls concepts.